The Principle Of Lex Specialis Derogat Legi Generalis In The Crime Of Diploma Forgery - Lindasari Lindasari (Faculty of Law, Universitas Lampung, 2025)
The issue addressed in this research is the enforcement of punishment for perpetrators of diploma forgery, which is not explicitly regulated in the Criminal Code but is implicitly and specifically addressed in Law No. 20 of 2003 concerning the National Education System. The aim of this research is to analyze the provisions related to the punishment of diploma forgery perpetrators and to understand the relevant criminal provisions in both the Criminal Code and Law No. 20 of 2003. The research employs a normative juridical method with a descriptive approach, utilizing both primary and secondary data sources. The findings indicate that, in Decision Number 43/Pid.B/2021/PN Liw, the public prosecutor applied the second alternative charge, namely Article 69, paragraph (1) of Law No. 20 of 2003 concerning the National Education System.